2022
DOI: 10.3390/app12031666
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Control System for Multilink Manipulators on Unmanned Underwater Vehicles Dynamically Positioned over Seafloor Objects

Abstract: This article considers an approach to synthesizing a multilevel system to control movements of a multilink manipulator (MM) mounted on an unmanned underwater vehicle (UUV) for performing autonomous manipulative operations in the mode of dynamic positioning over various objects on the seafloor. The system is based on an upgraded method that, using point clouds received from the machine vision systems (MVS), provides high-accuracy determination of the shape and location of the work object relative to UUV. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Процедура стыковки НПА начинается с определения пространственного положения и ориентации СП относительно НПА с помощью бортовых СТЗ, в качестве которых могут использоваться многолучевые сонары или стереокамеры. Известные системы [15,16]…”
Section: особенности формирования стыковочных траекторий манипулятора...unclassified
See 1 more Smart Citation
“…Процедура стыковки НПА начинается с определения пространственного положения и ориентации СП относительно НПА с помощью бортовых СТЗ, в качестве которых могут использоваться многолучевые сонары или стереокамеры. Известные системы [15,16]…”
Section: особенности формирования стыковочных траекторий манипулятора...unclassified
“…1. Основные параметры НПА и ММ приведены в таблице, а полное описание параметров и характеристик модели приведено в работе [15].…”
Section: исследование предложенного метода с помощью численного модел...unclassified
“…They found that the CFD approach was in excellent agreement with PIV measurements when simulating the essential unmeasured flow features required in the research and development process of UUVs. Konoplin et al [53] presented the development of a control system for multilink manipulators on UVVs. Their system was based on an improved method that utilized point clouds received from machine vision systems (MVSs).…”
Section: Uuv Control System Designmentioning
confidence: 99%
“…Currently, operator support systems are widely used for various ROV types [4,[17][18][19][20][21]. The information and control system of a ROV [4] graphically displays its spatial orientation and the configuration of the underwater multi-joint manipulator mounted on it.…”
Section: Introductionmentioning
confidence: 99%
“…The supervisory control system [20] was designed to significantly increase the level of automation of manipulative operations by constructing the trajectories of the manipulator's working tool along the surfaces of working objects based on the target instructions given by the operator. The multilevel control system of multi-link manipulators of ROVs described in [21] was designed for autonomous manip-ulation operations. The system uses point clouds received from machine vision systems, provides high-accuracy determination of the shape and location of the work object relative to vehicle and forms a trajectory along its surface, with possible silting, fouling, or deformation of the latter taken into account.…”
Section: Introductionmentioning
confidence: 99%